Sensorineural hearing loss in tubotympanic variety of chronic suppurative otitis media - Pramanik, Dhiman; Ahmed, Mesbah Uddin; Kabir, Abm Luthful; Rashid, Mohammad Harun Or; Haque, Mohammad Anamul; Ali, Md Asgar (Bangladesh Journal of Otorhinolaryngology, 2020)
Objectives: To determine whether chronic suppurative otitis media(CSOM) can cause Sensorineural hearing loss(SNHL) and to note its degree and its relation to duration of disease. Methods: This was a cross sectional study which was carried out in the departments of Otolaryngology and Head-Neck Surgery of Dhaka Medical College Hospital during the period of April’2012 to March’2013. A total number of 76 patients having unilateral CSOM were included in this study age ranging from 6 to 59 years after exclusion of other possible causes of SNHL such as meningitis, head injury, previous ear surgery and chronic noise exposure. The use of unilateral CSOM cases provided a contralateral ear to serve as a control. Bone conduction threshold elevation between diseased and control ear was considered as the indicator of inner ear damage. Results: In this series, CSOM was seen to be associated with sensorineural hearing loss. Significant threshold elevation was observed in relation to disease duration. Here bone conduction measurement in all frequencies (500Hz,1000Hz,2000Hz and 4000Hz) in diseased and uninvolved contralateral side showed elevation of bone conduction in diseased side and this elevation was significantly higher (p<0.001). The average bone conduction loss at 4kHz was higher than the average at the speech frequency range. Conclusion: This study suggests that CSOM can cause significant bone conduction threshold elevation and it should be considered when managing this problem. Early detection and prompt treatment may limit this potential handicap. Bangladesh J Otorhinolaryngol; April 2016; 22(1): 26-30